Pelatihan Cyber Security Awareness Kepada Masyarakat Menghadapi Perkembangan Kejahatan Siber - Irene Svinarky; Saragih, Saut Pintubipar; Ukas (ASOSIASI IDEBAHASA KEPRI, 2025)
Cyber crimes are on the rise recently. The attack has been very serious and needs to be tackled at all levels of society. Cybersecurity and Digital Privacy Training The target audience for this community service initiative in the Buana Bukit Permata residential area is adolescents. Although adolescents are known for their high levels of creativity, they often engage in self-expression on social media platforms by sharing content such as images, videos, or textual posts. The accessibility of social media through mobile devices, utilizing applications like TikTok, WhatsApp, Instagram, YouTube, and others, significantly facilitates this behavior.The objective of this initiative is to provide a comprehensive understanding and explanation of privacy, security, and the confidentiality of data and information in today’s digital landscape. The other goal is to educate participants on the legal provisions related to the Indonesian Electronic Information and Transactions Law (UUITE). Lecturers and students from Universitas Putera Batam, appointed as representatives, will deliver training and mentorship to the adolescents in Buana Bukit Permata. This initiative aims to enhance their skills in securing personal data and information to prevent misuse and its potential negative consequences. Relevant laws will also be explained to increase participants’ awareness of responsible internet usage. The training combines information technology knowledge with legal awareness, emphasizing both digital and legal literacy.